The behaviour of curved-crease foldcores under low-velocity impact loads. (15th January 2015) - Gattas, J.M.; You, Z.
Highlights: Numerical/experimental study of curved-crease (CC) foldcores under impact loads. CC-foldcores have higher energy-absorption than existing straight-crease foldcores. Two CC-foldcore types (tessellations) are examined – tessellation two is superior. An optimum CC-foldcore configuration had comparable performance to a honeycomb core. CC-foldcores exhibit some inertial strengthening under low-velocity impact loads. Abstract: The primary aim of this paper was to manufacture aluminium curved-crease foldcores and assess their behaviour under quasi-static compressive loads, relative to existing straight-crease foldcores and a honeycomb cores. Four foldcore types, standard, indented, and two curved-crease foldcore tessellations, were constructed with comparable density and height to a commercial honeycomb core. An experimental and numerical study of foldcore performance under quasi-static crush loads showed that all foldcore types were highly sensitive to geometric imperfections, and that curved-crease foldcores had significantly higher energy-absorption capability than straight-crease foldcores. Validated numerical methods were used in a comprehensive parametric study on curved-crease foldcore geometry, with two main findings. First, it was seen that altering the curved-crease foldcore tessellation did not provide significant energy-absorption capability beyond that achievable with direct changes to the core aspect ratio. Second, an optimum configuration of the curved-crease foldcore was found which appeared to offer a comparable out-of-plane strength, energy-absorption under quasi-static compressive loads, and stiffness to a honeycomb core. A brief numerical investigation into low-velocity impact loading showed that curved-crease foldcores were the only foldcore type that saw a substantial inertial strengthening under dynamic loading, although not to as large an extent as honeycomb.